Dependencies Management in Dynamically Updateable Component-Based System. - Alhazbi, Saleh; Jantan, Aman (Science Publications, 2007)
Component-based software systems achieve their functionalities through interaction between their components. Analyzing the dependencies between systems components is an essential task in system reconfiguration. This paper discusses dependencies analysis significance when updating component-based system dynamically. It presents a service-based matrix model and nested graph as approaches to capture components' dependencies; it discusses using dependencies analysis for safe dynamic updating in component-based software systems.